Transcriptional termination at the end of the early region of bacteriophages T3 and T7 is not affected by polarity suppressors. - Kiefer, M (1977)
Bacterial mutations of known rho genotype (psu-1 through psu-4) were shown to have no effect on transcriptional termination at the termination site at the end of the early region of T3 and T7 DNAs. Transcriptional termination was assayed in these bacterial mutants by comparing the patterns of late protein production produced by T3 and T7 amber I bacteriophage infection. All the rho (psu) mutants tested showed the same pattern of late protein production as the wild-type strain (rho+ or psu+) after T3 or T7 amber I infection. The presence of the mutant rho allele during bacteriophage infection, therefore, did not allow the host RNA polymerase to read through the terminator located at approximately 20% of the T3 and T7 genomes. These results suggest that rho factor may not be involved in reading of the T3 and T7 20% terminators in vivo.